Normative reference values for the 20 m shuttle-run test in a population-based sample of school-aged youth in Bogota, Colombia: the FUPRECOL study (2017)
Objectives: Our aim was to determine the normative reference values of cardiorespiratory fitness (CRF) and to establish the proportion of subjects with low CRF suggestive of future cardio-metabolic risk. Methods: A total of 7244 children and adolescents attending public schools in Bogota, Colombia (55.7% girls; age range of 9–17.9 years) participated in this study. We expressed CRF performance as the nearest stage (minute) completed and the estimated peak oxygen consumption (V?O2peak). Smoothed percentile curves were calculated. In addition, we present the prevalence of low CRF after applying a correction factor to account for the impact of Bogota's altitude (2625 m over sea level) on CRF assessment, and we calculated the number of participants who fell below health-related FITNESSGRAM cut-points for low CRF. Results: Shuttles and V?O2peak were higher in boys than in girls in all age groups. In boys, there were higher levels of performance with increasing age, with most gains between the ages of 13 and 17. The proportion of subjects with a low CRF, suggestive of future cardio-metabolic risk (health risk FITNESSGRAM category) was 31.5% (28.2% for boys and 34.1% for girls; X2 P =.001). After applying a 1.11 altitude correction factor, the overall prevalence of low CRF was 11.5% (9.6% for boys and 13.1% for girls; X2 P =.001). Conclusions: Our results provide sex- and age-specific normative reference standards for the 20 m shuttle-run test and estimated V?O2peak values in a large, population-based sample of schoolchildren from a large Latin-American city at high altitude. © 2016 The Authors American Journal of Human Biology Published by Wiley Periodicals, Inc.